2018
DOI: 10.1177/1078155218799850
|View full text |Cite
|
Sign up to set email alerts
|

Systemic therapy for relapsed/refractory meningioma: Is there potential for antiangiogenic agents?

Abstract: Effective therapies for relapsed/refractory meningioma after surgery and radiation therapy represent an unmet need. Most meningiomas are highly vascularized tumors and, therefore, potentially amenable to antiangiogenic therapy. Herein, we review comprehensively the scientific literature on systemic therapy options for relapsed, persistent or metastatic meningioma, not amenable to local therapy. Also, this review offers insights into the function of vascular endothelial growth factor/receptor pathway both in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…As such, if moderate dose escalation is pursued, using the physical advantage of the proton beam's properties to conform the dose deposition at a specific depth, the administration of PT in nonbenign meningioma should be considered ( Table 3). This has been the dose-strategy of all groups delivering PT for non-benign meningioma with doses up to 72 GyRBE (median/mean, [62][63][64][65][66][67][68] administered to these patients with no demonstrable increase the reported toxicity ( Table 2). The reported outcome after PT is good, with a median 5-year LC of 52% for WHO grade II-III tumors ( Table 2) but caution should be exercised not to overestimate these results due to the small number (16-35; median 23) of patients and short follow-up intervals of those series ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, if moderate dose escalation is pursued, using the physical advantage of the proton beam's properties to conform the dose deposition at a specific depth, the administration of PT in nonbenign meningioma should be considered ( Table 3). This has been the dose-strategy of all groups delivering PT for non-benign meningioma with doses up to 72 GyRBE (median/mean, [62][63][64][65][66][67][68] administered to these patients with no demonstrable increase the reported toxicity ( Table 2). The reported outcome after PT is good, with a median 5-year LC of 52% for WHO grade II-III tumors ( Table 2) but caution should be exercised not to overestimate these results due to the small number (16-35; median 23) of patients and short follow-up intervals of those series ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic strategy is often limited but salvage options may include additional surgery and/or re-treatment with a radiation-modality such as brachytherapy (65,66), photon radiotherapy including but not limited to normo-or hypo-fractionated radiotherapy/ radiosurgery, and PT (32). Systemic therapy, including the administration of check-point inhibitors (67), is usually ineffective and rarely translates into radiological objective responses, although WHO grades II-III meningioma patients appear to benefit more from chemotherapy than whose with grade I disease (5,68). Rechallenging these patients with radiation therapy again could potentially cause serious radiation-induced adverse events, as the organs at risk, including but not limited to the optic apparatus, brainstem and cochlea, have received a substantial dose of radiation already.…”
Section: Discussionmentioning
confidence: 99%
“…One study found in primary, non-NF2 mutated meningiomas, the pro-tumor inflammatory mediator IL-1β induced methylation of the NF2 promotor through various mediators that could act as novel targets ( 26 ). Other mutations like TRAF7, AKT1, KLF4, SMO, and PIK3CA were more recently described ( 27 , 28 ) and may represent therapeutic targets ( 29 – 31 ). In one particular study, grade I meningiomas harboring AKT1 mutations had predominantly M2-subtype infiltrating macrophages, indicating a locally immunosuppressed tumor microenvironment ( 32 ).…”
Section: Genetic Alterations Of Meningiomasmentioning
confidence: 99%
“…Several retrospective studies reported improved local tumor control following treatment with anti-angiogenic agents, such as bevacizumab, vatalanib, or sunitinib in recurrent, radioresistant, high-grade meningiomas [ 5 , 10 , 11 , 12 ]. The antiangiogenic effects of these agents are mainly based on blocking the vascular endothelial growth factor (VEGF) signaling pathway, one of the key mechanisms of tumorigenesis in general [ 13 ] and in the development of meningiomas in particular [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%